2010
DOI: 10.1007/s10811-010-9502-1
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of galactans from Gracilaria debilis and Gracilaria salicornia (Gracilariales, Rhodophyta) of Indian waters

Abstract: Superior quality non-methylated and low-sulphated galactans were extracted from two Indian agarophytes namely Gracilaria debilis and G. salicornia growing naturally along the west coast of India, using an eco-friendly method developed in our laboratory. The galactans were characterised by FT-IR, 13 C NMR, GC-MS, ICP, GPC and rheological measurements. G. debilis produced exclusively nonmethylated galactan exhibiting the greatest gel strength of 650±25 g cm −2 and lowest sulphate of 0.21±0.06%. On the contrary, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 17 publications
1
12
1
Order By: Relevance
“…The maximum gel strength (800 g cm −2 ) recorded in G. debilis was higher when compared with the previous reported values in G. debilis (335 g cm −2 , (Duckworth et al 1971; 650 g cm −2 , Mehta et al 2010). When comparing alkali treated other Indian agarophyte data (Meena and Siddhanta 2006), the maximum gel strength value of G. debilis was similar to that reported in Gelidiella acerosa (800 g cm −2 ) and Gracilaria crassa (800 g cm −2 ) and was higher than G. edulis (450 g cm − 2 ), G. corticata (100 g cm −2 ), and G. fergusonii (135 g cm −2 ).…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…The maximum gel strength (800 g cm −2 ) recorded in G. debilis was higher when compared with the previous reported values in G. debilis (335 g cm −2 , (Duckworth et al 1971; 650 g cm −2 , Mehta et al 2010). When comparing alkali treated other Indian agarophyte data (Meena and Siddhanta 2006), the maximum gel strength value of G. debilis was similar to that reported in Gelidiella acerosa (800 g cm −2 ) and Gracilaria crassa (800 g cm −2 ) and was higher than G. edulis (450 g cm − 2 ), G. corticata (100 g cm −2 ), and G. fergusonii (135 g cm −2 ).…”
Section: Discussioncontrasting
confidence: 73%
“…The agar from G. debilis is capable of forming a firm gel before treatment with alkali and had a significant amount of polysaccharide eluted in the water fraction and a lower sulfate content (0.8 %) which responsible for high gel strength agar (Duckworth et al 1971). 13 C NMR spectra of G. debilis agar confirmed that it is the presence of non-methylated polysaccharides which is responsible for high gel strength (Mehta et al 2010).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The EPS were hydrolysed in 2.0 M H 2 SO 4 (1008C, 6-8 h), and sugar was converted to alditol acetates by reduction followed by methylation (Mehta et al 2010). Alditol acetates were analysed and quantified on a GCMS-QP2010 (Shimadzu, Japan) using an SGE BP-225 capillary column (25 m length, 0.22 mm diameter and 0.25 mm thickness).…”
Section: Powder X-ray Diffraction Analysismentioning
confidence: 99%
“…Gel strength was measured in 1% (w/v) gel of modified Ag products and 1% (w/v) gel of the parent Ag at 20°C on a Nikkansui‐type gel tester (Kiya Seisakusho Ltd., Japan). Gelling and melting points were recorded following the reported method . Apparent viscosity was measured (in 1% w/v sample) on a Brookfield viscometer (DV‐II +Pro), using SC4–18 spindle at 60 rpm at 80°C.…”
Section: Methodsmentioning
confidence: 99%